2018
DOI: 10.2147/ott.s157295
|View full text |Cite
|
Sign up to set email alerts
|

Association of doublecortin-like kinase 1 with tumor aggressiveness and poor biochemical recurrence-free survival in prostate cancer

Abstract: BackgroundDoublecortin-like kinase 1 (DCLK1) has been proven to be involved in numerous tumors, while its role in prostate cancer (PCa) is still unclear. This study aimed at investigating the expression pattern and prognostic value of DCLK1 in PCa.Patients and methodsReal-time polymerase chain reaction and Western blot were employed to determine DCLK1 mRNA and protein levels in 25 paired fresh samples of PCa and benign prostatic hyperplasia (BPH) as well as in PCa cell lines. Immunohistochemistry (IHC) was als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…There are over 100 discrete forms of cancer, each with multiple causes (52). Numerous studies have found that DCLK1 is upregulated and acts as an oncogene in a range of cancers including pancreatic, colorectal, gastric, bladder, and breast cancer (7)(8)(9)(10)(11)(12)(13)(14). Due to the emerging body of evidence implicating DCLK1 in tumorigenesis, the protein appears to be a promising target for not just one, but for several types of cancers (15)(16)(17).…”
Section: Discussionmentioning
confidence: 99%
“…There are over 100 discrete forms of cancer, each with multiple causes (52). Numerous studies have found that DCLK1 is upregulated and acts as an oncogene in a range of cancers including pancreatic, colorectal, gastric, bladder, and breast cancer (7)(8)(9)(10)(11)(12)(13)(14). Due to the emerging body of evidence implicating DCLK1 in tumorigenesis, the protein appears to be a promising target for not just one, but for several types of cancers (15)(16)(17).…”
Section: Discussionmentioning
confidence: 99%
“…The macromolecular machine responsible for accurately segregating chromosomes during eukaryotic cell division is the bipolar mitotic spindle, a structure composed of dynamic microtubules organized by a multitude of MAPs (3,4). DCLK1, formerly known as DCAMKL1 and KIAA0369, is one such MAP that is also upregulated in a range of cancers, such as pancreatic, breast, bladder, colorectal, gastric, and hepatocellular carcinoma (5)(6)(7)(8)(9)(10)(11)(12)(13)(14). As a consequence, many studies have focused on developing small molecule inhibitors against DCLK1 kinase activity in an effort to control cancer growth (15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
“…These results suggest involvement of the processes regulated by KLF6 in response to BTZ treatment and bridging of those process may result in a treatment resistant phenotype. Apart from this top hit, a number of genes shown to be involved in proliferation of cancer cells were statistically significantly associated with BTZ induced methylation changes, including: ARHGAP26 38 , TBX2 39 , 40 , MAML3 41 , DCLK1 42 , 43 . The “GO cellular components” (Fig.…”
Section: Discussionmentioning
confidence: 99%